2011
DOI: 10.5194/angeo-29-1209-2011
|View full text |Cite
|
Sign up to set email alerts
|

Meteor radar measurements of MLT winds near the equatorial electro jet region over Thumba (8.5° N, 77° E): comparison with TIDI observations

Abstract: Abstract. The All-Sky interferometric meteor (SKYiMET) radar (MR) derived winds in the vicinity of the equatorial electrojet (EEJ) are discussed. As Thumba (8.5 • N, 77 • E; dip lat. 0.5 • N) is under the EEJ belt, there has been some debate on the reliability of the meteor radar derived winds near the EEJ height region. In this regard, the composite diurnal variations of zonal wind profiles in the mesosphere-lower thermosphere (MLT) region derived from TIMED Doppler Interferometer (TIDI) and ground based mete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…There have been a number of other comparisons between radar and satellite data sets [e.g., Portnyagin et al, 1999;Forbes et al, 2004;John et al, 2011;Killeen et al, 2006;Kishore Kumar et al, 2014;Guo and Lehmacher, 2009], but they were all short-term studies. We would like to point out here that there exist no previous long-term consistency studies using space-and ground-based observations of diurnal tide in the MLT region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a number of other comparisons between radar and satellite data sets [e.g., Portnyagin et al, 1999;Forbes et al, 2004;John et al, 2011;Killeen et al, 2006;Kishore Kumar et al, 2014;Guo and Lehmacher, 2009], but they were all short-term studies. We would like to point out here that there exist no previous long-term consistency studies using space-and ground-based observations of diurnal tide in the MLT region.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic and an extensive comparison between these two types of observations was carried out during the Climate And Weather of Sun-Earth System (CAWSES) program [Ward et al, 2010], albeit for a limited period, wherein tidal signatures sampled by ground-based observations were compared with those derived from a superposition of various tidal components retrieved from the satellite observations. There have been few other such reports as well [Kishore Kumar et al, 2014;John et al, 2011;Hasebe et al, 1997]. However, no study has been carried out to examine the agreement or disagreement between the two sets of tidal observations in longer time scales.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, by the received signal, the radar can measure the wind components in the meteor region, at about 70-110 km height. The methodology behind the estimation of winds is based on a complex correlation adopted to measure the signal phase differences between the receiving antennas in order to determine the echo arrival angle, and complex auto-and cross-correlation methods are used to obtain the rate of change of the relative phase in order to determine the radial velocity associated with the meteor trail, and then the meteor radar provides hourly zonal and meridional winds (John et al, 2011).…”
Section: Instrumentation and Methodologymentioning
confidence: 99%
“…It is suggested that this diurnal variation is due to external electric fields that are tidally driven. John et al (2011) compared the meteor radar winds and TIDI winds over Thumba equatorial station (8.5 N, 77 E) and concluded that Equatorial Electro Jet (EEJ) does not bias the radar measurements.…”
Section: Discussionmentioning
confidence: 99%